Construction of a nomogram prediction model for the influencing factors for spinal nerve injury in elderly parturients after intraspinal block - SHI Yu, YUE Xiuqin, WANG Zhen (精准医学杂志)
Objective To establish a nomogram model for predicting the influence factors for spinal nerve injury in elderly parturients after intraspinal block. Methods A total of 480 elderly parturients who received intraspinal block for delivery in our hospital from February 2019 to December 2021 were enrolled. The Lasso regression analysis was used to identify the influencing factors for spinal nerve injury after intraspinal block in elderly parturients, and the logistic regression analysis was used to construct a predictive model for the influencing factors for spinal nerve injury caused by intraspinal block in elderly parturients. R software was used to visualize the model and validate the nomogram model for the influencing factors for spinal nerve injury caused by intraspinal block in elderly parturients. Results Among the 480 elderly parturients, 62 experienced spinal nerve injury due to intraspinal block, and the incidence rate of spinal nerve injury was 12.92%. The Lasso regression analysis showed that whether the puncture process for anesthesia was smooth, anesthesia method, the amount of vaginal bleeding during delivery, the presence or absence of foreign body sensation in subarachnoid space during anesthesia, and the presence or absence of hypertension and diabetes were influencing factors for spinal nerve injury after intraspinal block. A prediction model was constructed based on the above factors, with a C-index of 0.754 and an AUC of 0.736. The calibration curve showed a good degree of fitness between the actual value and the predicted value, and the decision curve showed that at the threshold probability of 4%-67%, the nomogram model had a higher net benefit value in predicting spinal nerve injury after intraspinal block in elderly parturients. Conclusion Abnormal anesthesia puncture, combined spinal-epidural analgesia, vaginal bleeding ≥300 mL during delivery, foreign body sensation in su-barachnoid space during anesthesia, hypertension, and diabetes are influencing factors for spinal nerve injury after intraspinal block in elderly parturients. The nomogram model based on the above 6 predictive factors can help to identify the elderly parturients at a high risk of spinal nerve injury due to intraspinal block and formulate scientific prevention and control measures in advance.